Ice age climate, somatic capital, and the timing of the neolithic transition - Lothar Grall (Philipps-University Marburg, School of Business and Economics, 2016)
This paper proposes somatic capital as a hitherto neglected variable in the discussion of factors impacting the timing of the Neolithic transition. It develops an evolutionary growth theory that builds on the trade-off between the quantity and the quality of offspring. The theory suggests that harsh climatic conditions during the ice age raised skill-intensity of the environment and altered the evolutionary optimal allocation of resources from offspring quantity to offspring quality. Higher somatic investment in offspring increased the innovation capability of individuals and ultimately accelerated the rate of technological progress. Thus, the adaptive response triggered within human populations living in cold and harsh climate for thousands of years had a significant impact on the timing of the Neolithic transition. The theory further suggests that differential somatic investment can be identified as deep-rooted determinant of comparative economic development.
Keywords: J10; O10; O30; 330; Economic Growth; Human Evolution; Ice Age Climate; Neolithic Revolution; Out-of-Africa Expansion; Somatic Capital; Skill-Intensity; Technological Progress